Pregnancy during adjuvant tamoxifen therapy: A case of temporary interruption and postpartum metastatic recurrence (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2025)
Background: Limited data exist regarding recurrence risk in pregnant women with hormone receptor-positive breast cancer who temporarily discontinue endocrine therapy. Case presentation: A 37-year-old gravida 4, para 3, presented for antenatal care at 13 weeks’ gestation while on adjuvant tamoxifen, which she had taken for two months before conception. Examination revealed a fundal height of 18 weeks and a healed mastectomy scar. Ultrasonography confirmed a dichorionic diamniotic twin pregnancy. Tamoxifen was discontinued, and pregnancy proceeded uneventfully until spontaneous preterm delivery at 34 weeks. Both neonates were clinically normal. Tamoxifen was resumed postpartum; however, 5 months after delivery, the patient developed metastatic recurrence and subsequently succumbed. Conclusion: Pregnancy during breast cancer is not uncommon and poses complex clinical challenges. A multidisciplinary team is key to optimize maternal and neonatal outcomes.Keywords: breast cancer, endocrine therapy, metastasis, pregnancy, tamoxifen